Intelligent maintenance of complex systems: a fractional order approach - Carvajal, Ricardo Enrique Gutiérrez (2019)
Compete in the global market requires high quality of products with short time of manufacture, so it needs to minimize the time that the machinery is stopped, as well as a rapid quality control of manufactured products. These process are achieved by maintenance strategies that are strongly based on the subjective knowledge of an expert. In this work we use the proficiency of the fractional order calculus to approximate complex behavior with a few parameter, providing a new tool for quickly health evaluation.